2018
DOI: 10.1016/j.anifeedsci.2018.09.007
|View full text |Cite
|
Sign up to set email alerts
|

The relevance of functional amino acids to support the health of growing pigs

Abstract: On commercial farms, young growing pigs are frequently affected by health problems from multifactorial origins (e.g. environmental changes, biosecurity, management, and feed) that result in inflammation and activation of body defenses. Inflammation states alter animal metabolism in such a way that nutrients (particularly amino acids) are diverted from the use for growth towards the production of defense-related proteins and low-molecular-weight compounds (e.g., nitric oxide, H2S, and glutathione) for supportin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4
1
1

Relationship

5
5

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 156 publications
0
25
0
Order By: Relevance
“…However, this is a major challenge and, according to the authors’ knowledge, no ‘silver bullet’ has yet been identified to cope with PWD. Previous reviews have described nutritional and feeding strategies, such as supplementation with organic and inorganic acids [2], essential oils and herbs [3], and some types of probiotics, prebiotics and symbiotics [4], different dosages of essential amino acids [5] and nucleotides [6, 7], or the potential use of bacteriophages [8] to prevent and counteract PWD. In order to research effective strategies with the potential of counteracting PWD, a valid approach is to implement in vivo challenge models with ETEC infection.…”
Section: Introductionmentioning
confidence: 99%
“…However, this is a major challenge and, according to the authors’ knowledge, no ‘silver bullet’ has yet been identified to cope with PWD. Previous reviews have described nutritional and feeding strategies, such as supplementation with organic and inorganic acids [2], essential oils and herbs [3], and some types of probiotics, prebiotics and symbiotics [4], different dosages of essential amino acids [5] and nucleotides [6, 7], or the potential use of bacteriophages [8] to prevent and counteract PWD. In order to research effective strategies with the potential of counteracting PWD, a valid approach is to implement in vivo challenge models with ETEC infection.…”
Section: Introductionmentioning
confidence: 99%
“…This implies a consequent supplementation with synthetized essential amino acids (AA) to maintain performance 2 . Thus, AA requirement estimation has become pivotal in diet formulation to allow for a high feed efficiency and to maximize feed intake and growth rate in growing pigs, which implies the importance of knowing the metabolism of each AA and role also considering different pig genotypes and phenotypes 3 .…”
Section: Introductionmentioning
confidence: 99%
“…The results of the prediction of the pig feces microbiome functions obtained from 16S rRNA sequencing revealed that the pathway of serine and threonine metabolism was one of the most represented pathways identified by Tax4fun, which confirmed recent data on the functions of the pigs’ cecum and ileum microbiome (Umu et al 2020 ). In supporting this, it is known that in the large intestine of pigs a large variety of bacteria can use mucus and endogenous sources that are rich in threonine and serine (Le Floc’h et al 2018 ). That information can explain the always high utilization of L-serine in all the samples and dilutions observed in the present study.…”
Section: Discussionmentioning
confidence: 96%